Conductometric, physico-chemical, and biological activity investigations of a copper–indometacin complex - AbdulAziz A. Alayyafi; Kholoud Z. Ghanem; Modhi S. Almarri; Shereen E. Salem; Esam A. Gomaa; Elsayed M. AbouElleef (Green Chemistry Letters and Reviews)
Copper–indometacin (Cu-Indo) complex was prepared and X-ray diffraction, IR analysis, UV–V spectrophotometric analysis and thermal analysis of the formed (Cu-Indo) complex were used to characterize it. The formation constants for the complexation of CuCl2.2H2O and indometacin in methanol, ethanol, and their binary mixture with water were determined by the conductometric technique. Three stoichiometric complexes of copper–indometacin (1/2), (1/1), and (2/1) (M/L) were detected and their formation constants (Kf) were estimated by using the conductometric method and the Gibbs free energy change (ΔGf) was also estimated. The antimicrobial activities of indometacin and (Cu-Indo) complex have been studied using the disc diffusion method against Gram-negative bacteria (P. aeruginosa, E. coli, and K. pneumoniae), Gram-positive bacteria (S. aureus, B. cereus, and S. epidermidis), and fungi (C. albicans). In B. cereus, the (Cu-Indo) complex has a larger inhibitory zone (Gram-positive bacteria). As a result, it can be utilized to treat B. cereus bacteria (cytotoxicity testing was not conducted in this study).